Development of a novel loop-mediated isothermal amplification assay for ß-lactamase gene identification using clinical isolates of Gram-negative bacteria - Kim, Eun Jin; Lee, Jiwon; Yoon, Youngbae; Lee, Donghyun; Baek, Yeongjun; Takano, Chika; Sakai, Jun; Iijima, Takahiro; Kanamori, Dai; Gardner, Humphrey; McLaughlin, Robert E.; Kilgore, Paul E.; et al. (Frontiers in Cellular and Infection Microbiology, 2023)
Rapid evaluation of antimicrobial susceptibility is important in the treatment of nosocomial infections by Gram-negative bacteria, which increasingly carry carbapenemases and metallo-β-lactamases. We developed loop-mediated isothermal amplification (LAMP)-based assays for four β-lactamase genes (blaKPC, blaNDM-1, blaIMP-1 group, and blaVIM). The assays were evaluated using eight reference bacterial strains (Klebsiella pneumoniae, Escherichia coli, Pseudomonas aeruginosa, and Acinetobacter bereziniae) harboring six β-lactamase genes. A total of 55 Gram-negative bacterial strains, including 47 clinical P. aeruginosa isolates, fully characterized by next-generation sequencing (NGS), were used to evaluate the LAMP assays. The results were compared to those of conventional PCR. The LAMP assays were able to detect as few as 10 to 100 copies of a gene, compared to 10 to 104 copies for conventional PCR. The LAMP assay detected four β-lactamase genes with a sensitivity similar to that using purified DNA as the template in DNA-spiked urine, sputum, and blood specimens. By contrast, the sensitivity of PCR was 1- to 100-fold lower with DNA-spiked clinical specimens. Therefore, the LAMP assays were proved to be an appropriate tool for the detection of four β-lactamases.